Preserving apple (Malus domestica var. Anna) fruit bioactive substances using olive wastes extract-chitosan film coating - Ibrahim Khalifa; Hassan Barakat; Hamdy A. El-Mansy; Soliman A. Soliman (Information Processing in Agriculture, 2017)
Apple fruits have components of therapeutic nature. Such components, to a great extent, decline or decompose during post-harvest that negatively affect fruit shelf-life. Chitosan fruit-filming has proved useful in maintaining these compounds. This study aims, therefore, at enhancing Chitosan coating-film performance by mixing with some olive wastes extracts of leaf and pomace extracts. Apple fruits were sprayed with six different coating formulas including chitosan-water wax coating, in addition to the uncoated fruits. Then, the total phenolic, flavonoids, antioxidants, pigments, weight loss, decay area, and microstructure were assayed. The bioactive substances drastically changed in uncoated rather than coated fruits. Conversely, weight loss and decay area significantly increased in uncoated fruits. Amazingly, the addition of olive leaf extract to chitosan coating films meaningfully reduced the gradual decline in total phenolic, flavonoids and antioxidants. Olive pomace extract recorded the lowest influencing on anthocyanins during storage at 4 ± 1 °C for 35 d. Also, both olive leaf and pomace extracts enhanced the coating distribution, due to no pores were observed in the fruits’ surfaces. Decidedly, incorporation of olive leaf extracts with 2% into chitosan coating solution was the best formula comparable with the others. Thus, olive wastes extracts, incorporated into chitosan fruit coatings; relatively improve the nutritional quality of apple fruits during post-harvest.